Study of Thyroid Function Status in Type 2 Diabetic Patients - Alo, Kamrunnahar; Banik, Shyamal Chandra; Ahammed, Safayet; Yasmin, Ayesha; Rahman, Tania (KYAMC Journal, 2019)
Background: Thyroid dysfunction specially hypothyroidism may occur in type 2 diabetic patients. Objective: To observe thyroid function status in type 2 diabetic patients Materials and Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka from July 2016 to June 2017. Total 60 subjects including male and female, age ranged from 40 to 60 years were included in this study, among them 30 were non-diabetic subjects and 30 were type 2 diabetic patients. Results: In this study, mean serum TSH level was significantly (p<0.001) higher and serum FT4 level was significantly (p<0.01) lower in diabetic patients than that of apparently healthy non-diabetic subjects. Serum FT3 level was lower in type 2 diabetic patients in comparison to that of non-diabetic subjects but the difference was not statistically significant. However, among the diabetic patients 10% were subclinical hypothyroid and 6.67% were hypothyroid Conclusion: The present study reveals that hypothyroidism occurs in type 2 diabetic patients. So type 2 diabetic patients should measure thyroid hormone levels routinely to detect thyroid dysfunction. KYAMC Journal Vol. 10, No.-2, July 2019, Page 95-98